Bipolar plate for flow battery and preparation method of bipolar plate
By using graphite, carbon black and graphene as conductive agents, combined with polypropylene and other materials as adhesives, a liquid flow battery bipolar plate material with high conductivity, mechanical strength and corrosion resistance is prepared, which solves the limitations of existing materials in these aspects and extends the service life of the battery.
Patent Information
- Application Number
- CN202510082496.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-22
AI Technical Summary
The existing flow battery bipolar plate materials have limitations in corrosion resistance, strength, flexibility and conductivity, which affect the performance and life of the battery.
Graphite, carbon black and graphene are used as conductive agents, polypropylene, polyolefin elastomer and modified polyethylene are used as adhesives, and high-performance bipolar plate materials are formed by specific preparation methods and coupling agents.
It significantly improves the conductivity, mechanical strength, corrosion resistance and toughness of the bipolar plate, extends the service life of the battery, and enhances its adaptability under acid electrolyte.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of bipolar plates for liquid flow batteries, and in particular relates to a bipolar plate for a liquid flow battery and a preparation method thereof. Background Art
[0002] As a large-scale energy storage technology, flow batteries have received extensive attention and research in recent years. As a representative of them, all-vanadium flow batteries have the advantages of high energy efficiency, long cycle life, safety and environmental protection, and are particularly suitable for large-scale grid-connected use of renewable energy sources such as wind and solar power. In this battery system, the bipolar plate, as one of the key components, not only plays the role of separating the electrolyte, conducting electricity and supporting the battery structure, but also directly affects the performance, efficiency and life of the battery.
[0003] Traditional flow battery bipolar plate materials mostly use conductive materials such as metal or graphite, but these materials have certain limitations in terms of corrosion resistance, strength and flexibility. For example, although metal materials have good conductivity, they are easily corroded in acidic electrolytes, which affects the life of flow batteries; although graphite materials are corrosion-resistant, their strength and flexibility are relatively poor, and their resistivity is relatively high.
[0004] Therefore, developing a bipolar plate material that is corrosion-resistant, has a long lifespan, is strong, flexible, and has good conductivity has become an urgent need in the field of flow battery technology. Summary of the invention
[0005] The purpose of the present invention is to provide a bipolar plate for a liquid flow battery and a preparation method thereof, which not only improves the conductivity and mechanical strength of the bipolar plate of the liquid flow battery, ensures efficient transmission of current and structural stability, but also significantly improves its corrosion resistance and toughness, thereby extending the service life of the battery.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The raw materials for preparing the bipolar plate for the liquid flow battery include a conductive agent, an adhesive, a toughening agent, a coupling agent, and anhydrous ethanol.
[0008] Preferably, the mass ratio of the conductive agent to the adhesive is (1-3):1; further preferably, it is 2:1.
[0009] Preferably, the conductive agent includes one or more of graphite, graphene, carbon nanotubes, and carbon black; further preferably, graphite, carbon black, and graphene.
[0010] Preferably, the mass ratio of the graphite, carbon black and graphene is (15-20):(1-3):1; further preferably, it is 17:2:1.
[0011] Preferably, the graphite is expanded graphite, D50 < 10 μm, specific surface area > 25 m 2 / g.
[0012] In some preferred embodiments, the graphite is produced and sold by Qingdao Baixing Graphite Co., Ltd.
[0013] Preferably, the average particle size of the carbon black is 30-40 nm, and the specific surface area is 60-65 m 2 / g, resistivity ≤2.5Ω·cm.
[0014] In some preferred embodiments, the carbon black is purchased from Tianjin Moko New Material Technology Co., Ltd., ultrapure conductive carbon black SP.
[0015] Preferably, the graphene has a thickness of 0.7-0.9 nm, a monolayer rate of 78%-82%, and a resistivity of ≤0.3Ω·cm.
[0016] In some preferred embodiments, the graphene is purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0017] Selecting specific graphite, carbon black and graphene as conductive agents can enhance the mechanical properties while enhancing the conductivity of the bipolar plate. This may be because although graphite has excellent conductivity, it has low mechanical strength, high brittleness, and generally large particle size, which cannot be tightly stacked. Therefore, it not only affects the mechanical properties of the bipolar plate, but also affects its conductivity. In addition, its compatibility with the adhesive resin is poor, and the limitations of the layered structure and the uneven distribution state make the conductive network formed in the polymer relatively weak, making it more difficult to exert its conductivity. Although carbon black is not as conductive as graphite, its specific gravity is smaller and it occupies a larger volume fraction in the polymer, which is conducive to the formation of a denser conductive network in the polymer. The chain conductive structure formed by conductive carbon black in the polymer is more stable and continuous, which is conducive to the free movement of electrons and the improvement of conductive properties. Graphene has better conductivity than carbon black, but due to its flaky structure, it can better form a conductive network and improve the conductivity of the bipolar plate when used in combination with conductive carbon black in polymer resin. In addition, by controlling the particle size of graphite, carbon black and graphene, the mechanical strength and conductivity of the bipolar plate can be further improved. This may be because the conductive agent of different levels and sizes, small particles can be used as conductive agents for large particles, so that the conductive agent can be kept tightly packed, which can not only form a sufficiently good conductive network, but also increase the conductivity. The secondary filler with a particle size smaller than the main filler can effectively fill the gaps between the graphite flakes and reduce the resistivity of the composite bipolar plate. In addition, the tight stacking can also improve the mechanical strength of the bipolar plate. Carbon black can even be used as a reinforcing agent for the polymer matrix to further improve the mechanical properties. However, the poor interface bonding strength between the inorganic conductive agent and the organic adhesive will still affect the performance of the bipolar plate.
[0018] Preferably, the adhesive comprises polypropylene, polyolefin elastomer and modified polyethylene.
[0019] Preferably, the mass ratio of the polypropylene, the polyolefin elastomer and the modified polyethylene is (4-6):1:1.
[0020] Preferably, the polypropylene is copolymer polypropylene, the melt index at 190°C is 3-5g / 10min, and the Izod notched impact strength at 23°C is 50-55kJ / m 2 , the tensile yield strength is 23-25MPa.
[0021] In some preferred embodiments, the polypropylene is purchased from ExxonMobil TM Polypropylene 7032E3.
[0022] Preferably, the polyolefin elastomer has a melt index of 8-10 g / 10 min at 190° C., an ethylene content of 14%-16%, and an elongation at break of ≥800%.
[0023] In some preferred embodiments, the polyolefin elastomer is purchased from ExxonMobil, Vistamaxx TM 6202.
[0024] The use of polypropylene and polyolefin elastomers as adhesives can improve the toughness and impact resistance of bipolar plates while ensuring that the bending strength and tensile strength of bipolar plates meet the use requirements, and can also improve the life of liquid flow batteries. This may be because polypropylene and polyolefin elastomers are blended, and polyolefin elastomers are dispersed in the polypropylene matrix in the form of tiny particles. These tiny particles not only act as stress concentration points, but when the material is impacted by external forces, these stress concentration points will trigger energy dissipation mechanisms such as silver streaks and shear bands, thereby absorbing a large amount of impact energy and improving the toughness of the material. They can also effectively fill the tiny gaps in the polypropylene matrix, making the material structure more compact, thereby reducing the pores and defects inside the material, improving the overall density, and effectively preventing the penetration of liquid or gas in the bipolar plate, thereby improving the stability and cycle performance of the liquid flow battery. However, the addition of polyolefin elastomers will also reduce the bending strength and tensile strength of polypropylene to a certain extent, so the amount of polyolefin elastomer added needs to be controlled. However, the polymer surface energy is low and it is easy to be enriched on the surface of the bipolar plate, resulting in high contact resistance of the bipolar plate, affecting battery performance.
[0025] The preparation method of the modified polyethylene comprises the following steps: polyethylene, grafted monomer, grafted comonomer and initiator are uniformly stirred, melted and granulated in a single screw extruder, and extruded to obtain the modified polyethylene.
[0026] The polyethylene includes high-density polyethylene, low-density polyethylene, metallocene polyethylene, and low-density linear polyethylene; more preferably, high-density polyethylene and linear low-density polyethylene.
[0027] Preferably, the mass ratio of the high-density polyethylene to the linear low-density polyethylene is 1:(1-3); further preferably, it is 1:2.
[0028] Preferably, the high-density polyethylene has a melt index of 5-10 g / 10 min at 190°C, a flexural modulus of 1000-1500 MPa, and a cantilever beam notched impact strength of 5-7 kJ / m 2 .
[0029] In some preferred embodiments, the high density polyethylene is purchased from ExxonMobil TM High density polyethylene HMA 025.
[0030] Preferably, the linear low-density polyethylene has a melt index of 1-5 g / 10 min at 190°C and a density of 0.9-0.94 g / cm 3 , tear strength is 130-150kN / m.
[0031] In some preferred embodiments, the linear low-density polyethylene is purchased from Saudi Arabia SABIC, 318B.
[0032] Preferably, the grafting monomer includes one or more of glycidyl methacrylate and maleic anhydride; further preferably, glycidyl methacrylate and maleic anhydride.
[0033] Preferably, the molar ratio of glycidyl methacrylate to maleic anhydride is (1-3):1; more preferably, it is 2:1.
[0034] Preferably, the grafted comonomer includes one or more of styrene and acrylic acid; more preferably, it is styrene.
[0035] Preferably, the molar ratio of the grafted monomer to the grafted comonomer is (2-3):1; more preferably, it is 5:2.
[0036] Preferably, the added amount of the grafting monomer is 7.0%-10% of the mass of polyethylene.
[0037] Preferably, the initiator is dibenzoyl peroxide.
[0038] Preferably, the added amount of the initiator is 0.5%-1% of the mass of the polyethylene.
[0039] Preferably, the screw temperature of the single screw extruder is 170-190°C.
[0040] On the basis of polypropylene and polyolefin elastomers as adhesives, specific high-density polyethylene and linear low-density polyethylene are added, which not only greatly improves the toughness of the material and makes it more impact-resistant, but also optimizes the mechanical properties, so that the bipolar plate can meet more diverse application needs. This may be because on the one hand, the molecular chain structures of high-density polyethylene and linear low-density polyethylene are complementary. The molecular chain structure of high-density polyethylene is regular and has high crystallinity, while linear low-density polyethylene has good flexibility and impact resistance due to the short comonomer branches on its molecular chain. When they act together on polypropylene and polyolefin elastomers, this complementarity of molecular chain structure helps to optimize the overall performance of the bipolar plate. In addition, the addition of high-density polyethylene and linear low-density polyethylene will also change the crystallization behavior of the polypropylene and polyolefin elastomer composition, forming different crystalline phases, thereby affecting the performance of the bipolar plate. However, the compatibility between polypropylene and polyethylene is poor, and direct blending may affect the performance of the bipolar plate. By modifying high-density polyethylene and linear low-density polyethylene with specific grafted monomers and grafted comonomers, their compatibility with polypropylene can be improved, thereby avoiding the impact of poor compatibility on the blending effect and further affecting the performance of the bipolar plate.
[0041] Preferably, the toughening agent comprises carbon fiber.
[0042] Preferably, the carbon fiber has a diameter of 50-200 nm, a length of 1-15 μm, and a specific surface area of 18 m 2 / g.
[0043] In some preferred embodiments, the carbon fiber is purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0044] Preferably, the added amount of the toughening agent is 5%-10% of the total mass of the conductive agent and the adhesive.
[0045] Selecting specific carbon fibers as toughening agents can not only improve toughness and bending strength, but also control the amount of addition without weakening the conductivity of the bipolar plate. This may be because, on the one hand, carbon fibers can withstand and disperse external stress through their high strength and high modulus properties, thereby improving the toughness of the bipolar plate. On the other hand, the conductive properties of carbon fibers enable electrons to be smoothly transmitted between the fibers and the matrix material, keeping the conductive properties of the bipolar plate unaffected. However, the amount of carbon fiber added needs to be controlled. If excessive amounts are added, it may not only destroy the original conductive network, making it difficult for electrons to be transmitted in the material, thereby affecting the conductive properties of the bipolar plate, but may also destroy the continuity of the matrix material, making the bipolar plate more prone to fracture when subjected to external forces, resulting in increased brittleness and reduced toughness of the bipolar plate. In addition, excessive carbon fibers will affect the processing performance of the bipolar plate, causing the fluidity and formability during processing to deteriorate, resulting in an increase in defects during processing, thereby affecting the overall performance of the bipolar plate.
[0046] Preferably, the added amount of the coupling agent is 0.5%-1% of the total mass of the conductive agent and the adhesive.
[0047] Preferably, the coupling agent includes one or more of a silane coupling agent and a titanate coupling agent; further preferably, a silane coupling agent and a titanate coupling agent.
[0048] Preferably, the mass ratio of the silane coupling agent to the titanate coupling agent is 1:(0.5-2); further preferably, it is 1:1.
[0049] Preferably, the silane coupling agent includes one or more of KH-550, KH-560, KH-570, A-151, A-171, A-172, A-187, and Z-6040; more preferably, KH-550 and KH-560.
[0050] Preferably, the mass ratio of KH-550 to KH-560 is 1:(0.5-2); further preferably, it is 1:1.
[0051] Preferably, the titanate coupling agent is a pyrophosphate type monoalkoxy titanate, and the viscosity at 25°C is 250-350mm 2 / s, density ≥1.026g / cm 3 .
[0052] In some preferred embodiments, the titanate coupling agent is purchased from Yangzhou Yanyang New Material Technology Co., Ltd., TM-38S.
[0053] Selecting specific silane coupling agents and titanate coupling agents as coupling agents to modify the adhesive resin can improve the interfacial compatibility between the conductive agent and the adhesive, thereby greatly improving the various properties of the bipolar plate and its service life. This may be because first of all, the two silane coupling agents work synergistically to form a monolayer in the system by introducing active groups such as amino groups and epoxy groups, which can not only achieve a good coupling effect between the conductive agent and the adhesive, but also improve the bonding strength between the adhesive and the conductive agent, thereby improving the mechanical strength of the bipolar plate, and can also improve the weather resistance and chemical corrosion resistance of the bipolar plate, so that the prepared bipolar plate can be used in liquid flow batteries with strong acid electrolytes. However, the molecules of the silane coupling agent are small, and not only the molecular layer formed at the interface is dense, so that the improvement of the conductive performance is not obvious, but also it is easy to agglomerate. By adding a titanate coupling agent with a larger molecule to compound with the silane coupling agent, the effect of the addition of the coupling agent on the conductivity of the bipolar plate can be reduced. However, the long alkyl chains of the titanate coupling agent are easily entangled with the polymer resin, affecting the cross-linking between the resins and thus affecting the mechanical properties of the bipolar plate. Therefore, the selection of a compound of two coupling agents can improve the mechanical properties of the bipolar plate while improving its conductivity. In addition, in order to further reduce the impact of the addition of the coupling agent on the conductivity of the bipolar plate, the coupling agent is first coupled with the adhesive to reduce the bonding interface area between the conductive agent and the insulating material, thereby improving the mechanical strength while minimizing the impact on the conductive properties. Moreover, the amount of coupling agent added needs to be controlled to avoid excessive coupling agent accumulation at the interface, which affects the mechanical and conductive properties of the bipolar plate.
[0054] Preferably, the quality of the anhydrous ethanol is consistent with that of the adhesive.
[0055] The method for preparing the bipolar plate for the flow battery comprises the following steps:
[0056] S1. After the adhesive and anhydrous ethanol are mixed and dispersed evenly, a coupling agent is added, and ultrasonic dispersion is performed for 20-30 minutes. Then, a conductive agent and a toughening agent are added, and ultrasonic dispersion is performed for 2-3 hours. After drying and removing the anhydrous ethanol, the mixture is crushed through a 400-600 mesh sieve, and calcined at 170-190° C. for 20-30 minutes to obtain a composite pressed powder;
[0057] S2. After placing soft layers on the surfaces of the upper and lower compression molds, pour in the composite pressed powder, and hot-press and cure at a pressure of 5-15 MPa and a temperature of 195-205°C for 25-35 minutes, remove the soft layer on the surface to obtain a bipolar plate for a liquid flow battery.
[0058] Preferably, the soft layer is a fluorinated ethylene propylene copolymer, with an elongation at break of 250%-350%, a thickness of 20-30 μm, and a tensile strength of 20-22 MPa.
[0059] In some preferred embodiments, the soft layer is purchased from Airtech, A4000V, USA.
[0060] By covering the mold surface with a layer of specific fluorinated ethylene propylene copolymer when preparing the bipolar plate, the conductivity of the bipolar plate can be improved without affecting its mechanical strength. This may be because by placing a soft layer between the mold and the bipolar plate raw material, it is not only possible to reduce the accumulation of polymers on the surface of the bipolar plate by stress concentration during the hot pressing process, but also to expose the carbon fiber, thereby achieving the purpose of treating the resin-rich layer on the surface and reducing the surface contact resistance. It can also improve the smoothness of the surface of the bipolar plate. The surface of the traditional mold is rough, resulting in a high surface roughness of the prepared bipolar plate, which is prone to cracks, affecting the yield and mechanical properties of the bipolar plate. The buffering of the soft layer can form a bipolar plate with a smooth surface, thereby improving the yield and various properties of the bipolar plate.
[0061] Preferably, the power of the ultrasonic dispersion is 200-300W.
[0062] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0063] 1. The present invention provides a bipolar plate for a liquid flow battery. By selecting a specific raw material compound and combining it with a preparation method, it not only improves the conductivity and mechanical strength of the liquid flow battery bipolar plate, ensuring the efficient transmission of current and the stability of the structure, but also significantly improves its corrosion resistance and toughness, prolongs the service life of the battery, and enhances its adaptability in acid electrolytes, laying a solid foundation for the further development and application of liquid flow battery technology.
[0064] 2. The present invention selects specific graphite, carbon black and graphene as conductive agents, which can enhance the mechanical properties while enhancing the conductivity of the bipolar plate.
[0065] 3. The present invention selects specific carbon fiber as a toughening agent, which can not only improve toughness and bending strength, but also control the amount of addition without weakening the conductive properties of the bipolar plate.
[0066] 4. The present invention uses polypropylene and polyolefin elastomer as coupling agents, which can improve the toughness and impact resistance of the bipolar plate while ensuring that the bending strength and tensile strength of the bipolar plate meet the use requirements, and can also increase the life of the liquid flow battery.
[0067] 5. The present invention can improve the conductivity of the bipolar plate without affecting its mechanical strength by covering the mold surface with a layer of specific fluorinated ethylene propylene copolymer when preparing the bipolar plate. DETAILED DESCRIPTION
[0068] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0069] The raw materials used in the present invention are all commercially available, specifically:
[0070] Graphite is expanded graphite, D50<10μm, specific surface area>25m 2 / g, is a product produced and sold by Qingdao Baixing Graphite Co., Ltd.
[0071] The average particle size of carbon black is 30-40nm and the specific surface area is 60-65m 2 / g, resistivity ≤2.5Ω·cm, purchased from Tianjin Moko New Material Technology Co., Ltd., ultrapure conductive carbon black SP.
[0072] The graphene had a thickness of 0.7-0.9 nm, a monolayer rate of 78%-82%, and a resistivity of ≤0.3 Ω·cm, and was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0073] Polypropylene is copolymerized polypropylene, with a melt index of 3-5g / 10min at 190°C and an Izod notched impact strength of 50-55kJ / m at 23°C. 2 , tensile yield strength is 23-25Mpa, purchased from ExxonMobil, USA TM Polypropylene 7032E3.
[0074] The polyolefin elastomer has a melt index of 8-10 g / 10 min at 190°C, an ethylene content of 14%-16%, and an elongation at break of ≥800%, and is purchased from ExxonMobil, Vistamaxx, USA TM 6202.
[0075] The melt index of high-density polyethylene at 190°C is 5-10g / 10min, the flexural modulus is 1000-1500MPa, and the cantilever beam notched impact strength is 5-7kJ / m 2 , purchased from ExxonMobiITM high-density polyethylene HMA 025.
[0076] The melt index of linear low-density polyethylene at 190°C is 1-5g / 10min, and the density is 0.9-0.94g / cm 3 , tear strength is 130-150kN / m, purchased from Saudi Arabia SABIC, 318B.
[0077] The diameter of carbon fiber is 50-200nm, the length is 1-15μm, and the specific surface area is 18m 2 / g, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0078] Titanate coupling agent is a pyrophosphate type monoalkoxy titanate with a viscosity of 250-350mm at 25°C. 2 / s, density ≥1.026g / cm 3 , purchased from Yangzhou Yanyang New Material Technology Co., Ltd., TM-38S.
[0079] Fluorinated ethylene propylene copolymer, with an elongation at break of 250%-350%, a thickness of 20-30 μm, and a tensile strength of 20-22 MPa, was purchased from Airtech, USA, A4000V.
[0080] Example 1
[0081] This embodiment provides a bipolar plate for a liquid flow battery, and the raw materials for preparing the bipolar plate are a conductive agent, an adhesive, and anhydrous ethanol.
[0082] The mass ratio of the conductive agent to the adhesive is 2:1.
[0083] The conductive agent is graphite, carbon black and graphene, and the mass ratio is 17:2:1.
[0084] The adhesive is polypropylene, polyolefin elastomer and modified polyethylene, and the mass ratio is 5:1:1.
[0085] The preparation method of the modified polyethylene comprises the following steps: uniformly stirring polyethylene, grafted monomer, grafted comonomer and initiator, melting and granulating the mixture in a single screw extruder, and extruding the mixture to obtain the modified polyethylene.
[0086] The polyethylene is high-density polyethylene and linear low-density polyethylene, and the mass ratio is 1:2.
[0087] The grafting monomers are glycidyl methacrylate and maleic anhydride, with a molar ratio of 2:1.
[0088] The grafted comonomer is styrene.
[0089] The molar ratio of the grafted monomer to the grafted comonomer is 5:2.
[0090] The added amount of the grafting monomer is 8.5% of the weight of the polyethylene.
[0091] The initiator is dibenzoyl peroxide.
[0092] The added amount of the initiator is 0.7% of the weight of the polyethylene.
[0093] The screw temperature of the single screw extruder was 180°C.
[0094] The toughening agent is carbon fiber.
[0095] The added amount of the toughening agent is 8% of the total mass of the conductive agent and the adhesive.
[0096] The added amount of the coupling agent is 0.8% of the total mass of the conductive agent and the adhesive.
[0097] The coupling agent is a silane coupling agent and a titanate coupling agent, and the mass ratio is 1:1.
[0098] The silane coupling agents are KH-550 and KH-560, with a mass ratio of 1:1.
[0099] The quality of the anhydrous ethanol is consistent with that of the adhesive.
[0100] The method for preparing the bipolar plate for the liquid flow battery comprises the following steps:
[0101] S1. After the adhesive and anhydrous ethanol are mixed and dispersed evenly, a coupling agent is added, and ultrasonic dispersion is performed for 25 minutes. Then, a conductive agent and a toughening agent are added, and ultrasonic dispersion is performed for 2.5 hours. After that, anhydrous ethanol is removed by drying, the mixture is crushed through a 500-mesh sieve, and calcined at 180° C. for 25 minutes to obtain a composite pressed powder;
[0102] S2. After placing soft layers on the surfaces of the upper and lower compression molds, pour in the composite pressed powder, and after hot pressing and curing for 30 minutes at a pressure of 10 MPa and a temperature of 200°C, remove the surface soft layer to obtain a bipolar plate for a liquid flow battery.
[0103] The soft layer is a fluorinated ethylene propylene copolymer.
[0104] The power of the ultrasonic dispersion is 250W.
[0105] Example 2
[0106] The difference between this embodiment and embodiment 1 is that the mass ratio of the conductive agent to the adhesive is 5:2.
[0107] Comparative Example 1
[0108] The difference between this comparative example and Example 1 is that the conductive agent is graphite and graphene, and the mass ratio is 17:3.
[0109] Comparative Example 2
[0110] The difference between this comparative example and Example 1 is that the average radial size of the graphene is 20-30 μm, D50<10 μm, and it is purchased from Shanghai MacLean Biochemical Technology Co., Ltd., G992594 graphene experimental grade powder.
[0111] Comparative Example 3
[0112] The difference between this comparative example and Example 1 is that the coupling agent is a silane coupling agent.
[0113] Comparative Example 4
[0114] The difference between this comparative example and Example 1 is that the added amount of the coupling agent is 1.5% of the total mass of the conductive agent and the adhesive.
[0115] Comparative Example 5
[0116] The difference between this comparative example and Example 1 is that the added amount of the toughening agent is 15% of the total mass of the conductive agent and the adhesive.
[0117] Comparative Example 6
[0118] The difference between this comparative example and Example 1 is that the adhesive is polypropylene.
[0119] Comparative Example 7
[0120] The difference between this comparative example and Example 1 is that the adhesive is polypropylene, polyolefin elastomer and polyethylene, and the mass ratio is 5:1:1.
[0121] Comparative Example 8
[0122] The difference between this comparative example and Example 1 is that the preparation method of the bipolar plate for the liquid flow battery comprises the following steps:
[0123] S1. After the adhesive and anhydrous ethanol are mixed and dispersed evenly, a coupling agent is added, and ultrasonic dispersion is performed for 25 minutes. Then, a conductive agent and a toughening agent are added, and ultrasonic dispersion is performed for 2.5 hours. After that, anhydrous ethanol is removed by drying, the mixture is crushed through a 500-mesh sieve, and calcined at 180° C. for 25 minutes to obtain a composite pressed powder;
[0124] S2. Pour the composite pressed powder into the upper and lower compression molds, and hot press and cure for 30 minutes at a pressure of 10 MPa and a temperature of 200° C. to obtain a bipolar plate for a liquid flow battery.
[0125] Comparative Example 9
[0126] The difference between this comparative example and Example 1 is that the preparation method of the bipolar plate for the liquid flow battery comprises the following steps:
[0127] S1. After the conductive agent and anhydrous ethanol are mixed and dispersed evenly, a coupling agent is added, and ultrasonic dispersion is performed for 25 minutes. Then, an adhesive and a toughening agent are added, and ultrasonic dispersion is performed for 2.5 hours. After that, anhydrous ethanol is removed by drying, the mixture is crushed through a 500-mesh sieve, and calcined at 180° C. for 25 minutes to obtain a composite pressed powder;
[0128] S2. After placing soft layers on the surfaces of the upper and lower compression molds, pour in the composite pressed powder, and after hot pressing and curing for 30 minutes at a pressure of 10 MPa and a temperature of 200°C, remove the surface soft layer to obtain a bipolar plate for a liquid flow battery.
[0129] Performance Testing
[0130] The contact resistance (mΩ·cm2) and bending strength (MPa) of the bipolar plate were tested with reference to NB / T 42007-2013 "Test Methods for Bipolar Plates for All-Vanadium Flow Batteries". The planar conductivity (S / cm) of the bipolar plate was tested by a dual-electric four-probe resistivity tester. The elongation at break (%) of the bipolar plate was tested with reference to GB / T 2567-2008 "Test Methods for Properties of Resin Castings". The energy efficiency (%) after 200 cycles at a current density of 100mA / cm2 was tested with reference to the method in Huang Yu's paper "The Effect of Thickness of Bipolar Plates for Vanadium Flow Batteries on Battery Performance". The results are shown in Table 1.
[0131] Table 1 Measurement results
[0132] Contact resistance Bending Strength Conductivity Elongation at break Energy efficiency Example 1 20.70 38.70 658.90 128 87.75 Example 2 19.95 38.04 666.82 124 86.29 Comparative Example 1 26.68 33.36 471.73 111 86.68 Comparative Example 2 23.50 35.65 534.98 115 86.49 Comparative Example 3 22.81 39.23 584.47 118 84.16 Comparative Example 4 25.66 35.57 495.35 112 82.89 Comparative Example 5 24.28 33.67 516.01 109 81.73 Comparative Example 6 21.47 39.54 597.84 102 81.49 Comparative Example 7 21.62 35.14 584.92 106 81.20 Comparative Example 8 29.16 32.60 411.45 108 82.38 Comparative Example 9 23.48 37.89 540.07 121 85.01
[0133] According to statistics, the bipolar plates for flow batteries prepared in Examples 1 to 2 of the present invention have low contact resistance and high conductivity, indicating excellent electrical conductivity, high bending strength, indicating excellent mechanical properties, high elongation at break, indicating certain impact resistance, and high energy efficiency, indicating good cycle stability and corrosion resistance. Comparative Example 1 does not add carbon black, Comparative Example 2 does not have the right graphene size, Comparative Example 3 does not add titanate coupling agent, Comparative Example 4 adds excessive coupling agent, Comparative Example 5 adds excessive toughening agent, Comparative Example 6 only adds polypropylene as an adhesive, Comparative Example 7 does not modify polyethylene, Comparative Example 8 does not use a soft layer for preparation, Comparative Example 9 first couples the coupling agent with the conductive agent, and the prepared bipolar plate has insufficient electrical conductivity, mechanical properties, impact resistance, and cycle stability. Therefore, the bipolar plate for flow batteries prepared by the raw materials and methods described in this application not only has excellent electrical conductivity and mechanical strength, ensuring efficient current transmission and structural stability, but also significantly improves corrosion resistance and toughness, and extends the service life of the battery.
[0134] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A bipolar plate for a liquid flow battery, characterized in that: The raw materials for its preparation include conductive agent, adhesive, toughening agent, coupling agent and anhydrous ethanol; The conductive agent includes one or more of graphite, graphene, carbon nanotubes, and carbon black; The graphite is expanded graphite, D50<10μm, specific surface area>25m 2 / g; The average particle size of the carbon black is 30-40nm, and the specific surface area is 60-65m 2 / g, resistivity ≤2.5Ω·cm; The graphene has a thickness of 0.7-0.9 nm, a single layer rate of 78%-82%, and a resistivity of ≤0.3Ω·cm.
2. The bipolar plate for a liquid flow battery according to claim 1, characterized in that: The mass ratio of the conductive agent to the adhesive is (1-3):
1.
3. The bipolar plate for a liquid flow battery according to claim 1, characterized in that: The adhesive includes polypropylene, polyolefin elastomer and modified polyethylene.
4. The bipolar plate for a liquid flow battery according to claim 3, characterized in that: The polypropylene is copolymerized polypropylene, the melt index at 190°C is 3-5g / 10min, and the Izod notched impact strength at 23°C is 50-55kJ / m 2 , the tensile yield strength is 23-25MPa.
5. The bipolar plate for a liquid flow battery according to claim 3, characterized in that: The polyolefin elastomer has a melting index of 8-10 g / 10 min at 190° C., an ethylene content of 14%-16%, and an elongation at break of ≥800%.
6. The bipolar plate for a liquid flow battery according to claim 1, characterized in that: The toughening agent includes carbon fiber; the carbon fiber has a diameter of 50-200nm, a length of 1-15μm, and a specific surface area of 18m 2 / g.
7. The bipolar plate for a liquid flow battery according to claim 1, characterized in that: The coupling agent includes one or more of a silane coupling agent and a titanate coupling agent.
8. The bipolar plate for a liquid flow battery according to claim 7, characterized in that: The silane coupling agent includes one or more of KH-550, KH-560, KH-570, A-151, A-171, A-172, A-187, and Z-6040.
9. The bipolar plate for a liquid flow battery according to claim 7, characterized in that: The titanate coupling agent is a pyrophosphate type monoalkoxy titanate, and the viscosity at 25°C is 250-350mm 2 / s, density ≥1.026g / cm 3 .
10. A method for preparing a bipolar plate for a flow battery according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. After the adhesive and anhydrous ethanol are mixed and dispersed evenly, a coupling agent is added, and ultrasonic dispersion is performed for 20-30 minutes. Then, a conductive agent and a toughening agent are added, and ultrasonic dispersion is performed for 2-3 hours. After drying and removing the anhydrous ethanol, the mixture is crushed through a 400-600 mesh sieve, and calcined at 170-190° C. for 20-30 minutes to obtain a composite pressed powder; S2. After placing soft layers on the surfaces of the upper and lower compression molds, pour in the composite pressed powder, and hot-press and cure at a pressure of 5-15 MPa and a temperature of 195-205°C for 25-35 minutes, remove the soft layer on the surface to obtain a bipolar plate for a liquid flow battery.